The effect of education on oral health students’ attitudes in Australia and New Zealand - Tanny, Liyana; Komabayashi, Takashi; Long, D. Leann; Yahata, Yoshio; Moffat, Susan M.; Tãne, Helen (European Journal of Dentistry, 2016)
Objective: The aim of this study was to evaluate the oral health attitudes and behavior of students in the oral health curriculum in Australia and New Zealand. Materials and Methods: The Hiroshima University - Dental Behavioral Inventory was administered to students in the first (year 1) and final years (year 3) of the oral health curriculum at Charles Sturt University in Australia and the University of Otago in New Zealand. A total of fifty-two year 1 students and forty-five year 3 students completed English version of the questionnaire in 2013. The responses were statistically analyzed by Fisher's exact tests and exact logistic regression models. Results: The responses of students in years 1 and 3 differed significantly for “I worry about the color of my teeth” at Charles Sturt University and at the University Otago, for “I think my teeth are getting worse despite my daily brushing,” “I put off going to the dentist until I have a toothache,” and “I don't feel I've brushed well unless I brush with strong strokes.” The estimated odds ratios from the exact logistic regression models showed that year 1 students were more likely to agree with above-mentioned four questions. Conclusions: Oral Health students who had been educated in a 3-year oral health curriculum in Australia and New Zealand had more positive attitudes and behaviors related oral health than did students at the beginning of their curriculum.
Keywords: Curriculum; oral health attitude; oral health behaviors